Discovery of protein biomarkers for venous thromboembolism in non-small cell lung cancer patients through data-independent acquisition mass spectrometry - Liu, Yanhong; Gao, Lan; Fan, Yanru; Ma, Rufei; An, Yunxia; Chen, Guanghui; Xie, Yan (Frontiers in Oncology, 2023)
Objective Non-small cell lung cancer (NSCLC) patients present a high incidence of venous thromboembolism (VTE) with poor prognosis. It is crucial to identify and diagnose VTE early. The study aimed to identify potential protein biomarkers and mechanism of VTE in NSCLC patients via proteomics research. Methods Proteomic analysis of the human plasma was performed through data-independent acquisition mass spectrometry for 20 NSCLC patients with VTE, and 15 NSCLC patients without VTE. Significantly differentially expressed proteins were analyzed by multiple bioinformatics method for further biomarker analysis. Results A total of 280 differentially expressed proteins were identified in VTE and non-VTE patients, where 42 were upregulated and 238 were downregulated. These proteins were involved in acute-phase response, cytokine production, neutrophil migration and other biological processes related to VTE and inflammation. Five proteins including SAA1, S100A8, LBP, HP and LDHB had significant change between VTE and non-VTE patients, with the area under the curve (AUC) were 0.8067, 0.8308, 0.7767, 0.8021, 0.8533, respectively. Conclusions SAA1, S100A8, LBP, HP and LDHB may serve as potential plasma biomarkers for diagnosis VTE in NSCLC patients.